2021
DOI: 10.1186/s40594-021-00285-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and belonging: the impact of a university makerspace

Abstract: Background In recent years, makerspaces have become increasingly common venues of STEM education and are rapidly being incorporated into undergraduate programs. These spaces give students and instructors access to advanced design technology and facilitate the incorporation of a wide variety of projects into the curriculum; however, their impacts on students are not yet fully understood. Using matched survey responses (i.e., repeated measures) from undergraduate students enrolled in engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
(89 reference statements)
0
33
0
1
Order By: Relevance
“…While designing and creating teaching and learning materials, the preservice teachers need to use and reflect on a variety of digital tools they can use to develop his or her ideas and are additionally impelled to consider how their products will affect the learning process of the learners for which they are designed. It is suggested that especially intrinsic motivation and self‐efficacy are fostered while learning by creating in a makerspace (e.g., Andrews et al, 2021). To support the implementation of the project, the pedagogical makerspace provides an open offer that includes additional self‐learning materials such as tool tutorials, workshops and support staff who can assist with technical problems.…”
Section: Methodsmentioning
confidence: 99%
“…While designing and creating teaching and learning materials, the preservice teachers need to use and reflect on a variety of digital tools they can use to develop his or her ideas and are additionally impelled to consider how their products will affect the learning process of the learners for which they are designed. It is suggested that especially intrinsic motivation and self‐efficacy are fostered while learning by creating in a makerspace (e.g., Andrews et al, 2021). To support the implementation of the project, the pedagogical makerspace provides an open offer that includes additional self‐learning materials such as tool tutorials, workshops and support staff who can assist with technical problems.…”
Section: Methodsmentioning
confidence: 99%
“…The makerspace of the School of Civil Engineering became the space for tinkering and the corresponding development of such activities. Makerspaces have become increasingly common venues of STEM and STEAM education and are rapidly being incorporated into undergraduate programs [33][34][35][36][37]. These spaces give students and instructors access to advanced design technology and facilitate the incorporation of a wide variety of projects into the curriculum.…”
Section: Literature Review: the Role Of Makerspacesmentioning
confidence: 99%
“…Makerspaces are places where students can engage in these hands-on making experiences (Hatch, 2013). Pedagogical approaches used in making and makerspaces can support students' agency; inquiry with materials; approaches to design and problem solving; design self-efficacy; science, technology, engineering, and mathematics (STEM) literacy practices; and engagement in different and more equitable forms of STEM learning (Andrews et al, 2021;Bevan et al, 2015;Calabrese Barton & Tan, 2018;Martin et al, 2018;Puckett & Gravel, 2020;Sheridan et al, 2014; Page 2 of 22 Gravel and Puckett International Journal of STEM Education (2023) 10:7 2019). Schools are increasingly implementing making as a STEM reform effort (Martin, 2015), yet there are still relatively few studies that explore how schools adopt maker education in K-12 settings (e.g., Hansen et al, 2019;Kim & Sinatra, 2018;Rouse & Gillespie Rouse, 2022;Stornaiuolo & Nichols, 2018;Vongkulluksn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%